2015
DOI: 10.1371/journal.pone.0126352
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminal Clostridium perfringens Enterotoxin-Mediated Antigen Delivery for Nasal Pneumococcal Vaccine

Abstract: Efficient vaccine delivery to mucosal tissues including mucosa-associated lymphoid tissues is essential for the development of mucosal vaccine. We previously reported that claudin-4 was highly expressed on the epithelium of nasopharynx-associated lymphoid tissue (NALT) and thus claudin-4-targeting using C-terminal fragment of Clostridium perfringens enterotoxin (C-CPE) effectively delivered fused antigen to NALT and consequently induced antigen-specific immune responses. In this study, we applied the C-CPE-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 45 publications
3
41
0
Order By: Relevance
“…26 Furthermore, an antigen-delivery method has been developed that targets claudin-4, a major cell-adhesion molecule in tight junctions that is highly expressed on the epithelium of nasopharynx-associated lymphoid tissue. 27 PspA–C-CPE, a fusion protein comprising PspA and a C-terminal fragment of Clostridium perfringens enterotoxin (C-CPE), which binds claudin-4, efficiently attached to nasopharynx-associated lymphoid epithelium after nasal administration to mice. 27 In addition, PspA–C-CPE effectively induced antigen-specific immune responses, and PspA-specific antibodies were elevated not only as IgG in the serum and bronchoalveolar lavage fluid but also as IgA in nasal washes and bronchoalveolar lavage fluid.…”
Section: Development Of a Nanogel-based Nasal Vaccine Against Pneumoniamentioning
confidence: 99%
See 2 more Smart Citations
“…26 Furthermore, an antigen-delivery method has been developed that targets claudin-4, a major cell-adhesion molecule in tight junctions that is highly expressed on the epithelium of nasopharynx-associated lymphoid tissue. 27 PspA–C-CPE, a fusion protein comprising PspA and a C-terminal fragment of Clostridium perfringens enterotoxin (C-CPE), which binds claudin-4, efficiently attached to nasopharynx-associated lymphoid epithelium after nasal administration to mice. 27 In addition, PspA–C-CPE effectively induced antigen-specific immune responses, and PspA-specific antibodies were elevated not only as IgG in the serum and bronchoalveolar lavage fluid but also as IgA in nasal washes and bronchoalveolar lavage fluid.…”
Section: Development Of a Nanogel-based Nasal Vaccine Against Pneumoniamentioning
confidence: 99%
“…27 PspA–C-CPE, a fusion protein comprising PspA and a C-terminal fragment of Clostridium perfringens enterotoxin (C-CPE), which binds claudin-4, efficiently attached to nasopharynx-associated lymphoid epithelium after nasal administration to mice. 27 In addition, PspA–C-CPE effectively induced antigen-specific immune responses, and PspA-specific antibodies were elevated not only as IgG in the serum and bronchoalveolar lavage fluid but also as IgA in nasal washes and bronchoalveolar lavage fluid. Consequently, mice nasally vaccinated with PspA–C-CPE were protected against pneumococcal infection.…”
Section: Development Of a Nanogel-based Nasal Vaccine Against Pneumoniamentioning
confidence: 99%
See 1 more Smart Citation
“…Given the critical role of M cells in mucosal immunity, targeting ligands to M cells is an attractive strategy for improving mucosal immunizations. Interestingly, M cells show significant expression of claudin-4, a strong CPE receptor [63]. While fusion proteins containing active CPE cannot be used for immunizations due to toxicity issues, the presence of claudin-4 on M cells suggested that a targeting strategy using nontoxic, but claudin binding-capable, CPE derivatives might be useful for preparing fusion proteins for use in improved mucosal vaccines.…”
Section: Applications From Understanding Cpe: Claudin Receptor Intmentioning
confidence: 99%
“…Several published studies now support this approach. For example, C-CPE has been fused with pneumococcal surface protein A (PspA), an important antigen for inducing protective immunity against Streptococcus pneumoniae infection [63]. When administered intranasally, this vaccine induced immune responses that were protective against infection by this important bacterial pathogen.…”
Section: Applications From Understanding Cpe: Claudin Receptor Intmentioning
confidence: 99%